Penguatan Literasi Digital bagi Guru Sekolah Dasar dalam Pengembangan Media Pembelajaran Berbasis Canva - Riyadi, Riyadi; Triyani, Septi; Bayu Kurniawan, Sandra; Chumdari, Chumdari (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
Teachers' ability to develop digital learning media is a crucial factor in supporting successful learning, along with the advancement of technology and information. However, the integration of digital literacy into learning is still rarely implemented, especially in elementary schools. Interviews with teachers at SDN Siwal revealed that few teachers use digital learning media, including Canva. Therefore, this community service activity aims to improve teachers' pedagogical skills by developing Canva-based digital learning media to optimize the integration of digital literacy into learning. This activity was conducted at SDN Siwal, Sukoharjo. The method used is a collaborative approach. The methods used are training that includes: brainstorming methods, expert presentations, discussions, assignments, dissemination, and mentoring. This community service activity consists of three stages: preparation, implementation, and program evaluation. The results of this activity show an increase in teacher understanding in developing Canva-based learning media, as indicated by an increase in the average score of participants from the pre-test to the post-test. Furthermore, better changes can also be seen in the results of the participants' work. The results of this activity also demonstrate that in developing Canva-based digital learning media, teachers need to adapt to learning needs to achieve learning objectives. Based on the results of this community service activity, it can be concluded that training and mentoring for teachers in developing digital learning media can be an effort to improve digital literacy skills, which include the ability to use technology critically, ethically, and creatively for teachers.